Ways of Improvement Import Operations Management «Planet of Equipment» LLC, Kyiv (Economics and region, 2020)
Today, a large number of Ukrainian enterprises are actively involved in foreign economic activity. The organization of import activity of the enterprise is a very difficult and responsible work. This requires careful consideration of issues such as market conditions, evaluating potential sellers, establishing business contacts with them, negotiating, signing agreements, and more. The article analyzes the activity of Planet Equipment LLC, Kyiv. Weaknesses of import operations identified. Measures have been taken to improve the import business such as: marketing, after sales service and price. In order to evaluate the feasibility of implementing the developed recommendations in the activities of Planet Equipment LLC, a forecast of import activity indicators as well as economic activity in general was made.
Keywords: foreign economic activity; enterprise; import operations; forecast